Association between quality of care indicators and clinical outcomes in patients undergoing transcatheter aortic valve implantation : insights from SWEDEHEART - Nilsson, Konrad; James, Stefan; Backes, Jenny; Götberg, Matthias; Hagström, Henrik; Batra, Gorav (European Heart Journal - Quality of Care and Clinical Outcomes, 2026)
Aims: The European Society of Cardiology (ESC) has developed quality indicators (QIs) specifically for evaluating the care and outcomes for patients undergoing transcatheter aortic valve implantation (TAVI). The aim of this study was to evaluate TAVI care in all patients undergoing such procedures in Sweden using the ESC 2023 QIs for TAVI. Methods and results: We used the Swedish Transcatheter Cardiac Intervention Registry to identify all TAVI procedures performed in Swedish centres (n = 8) between 2008 and 2021. 8524 patients (median 82 years, 52.8% male) were included. In total, 24 (88.8%) of the 27 QIs could be captured from the available registry data. The attainment levels were generally high [median 97.8%, interquartile range (IQR) 91.3–100%] with small variations in attainment levels between centres. The greatest variations were observed in the QIs related to patients undergoing TAVI through transfemoral route (median 90.3%, IQR 85.6–96.9%), and in the proportion undergoing transfemoral TAVI without general anaesthesia (median 87.6%, IQR 57.1–94.4%). In total, 80% of the QIs were associated with 1-year all-cause mortality, and 85% with 1-year cardiovascular mortality. The QIs with greatest impact on 1-year mortality were the absence of coronary obstruction (adjusted HR 0.12; 95% CI 0.07–0.22), in-hospital stroke (adjusted HR 0.25; 95% CI 0.18–0.33) and no new dialysis (adjusted HR 0.25; 95% CI 0.15–0.41). Conclusion: In this study, the majority of the QIs were associated with both all-cause and cardiovascular mortality. Hence, the ESC 2023 QIs for TAVI may serve as a valuable tool for evaluating TAVI care, benchmarking performance, and improving patient outcomes.
Keywords: Cardiovascular outcomes; Implementation; Mortality; Quality indicators; Quality of care; Transcatheter aortic valve implantation